Relationship between QRS duration on admission electrocardiogram and angiographic severity of coronary artery disease in patients with acute anterior myocardial infarction - Taher, M. Abu; Islam, M. Daharul; Jahedul Islam, M.; Khairuzzaman, M. (International Journal of Research in Medical Sciences, 2025)
Background: Early risk stratification in myocardial infarction (MI) is crucial, but the prognostic role of admission electrocardiography (ECG) findings remains underexplored. This study evaluated the relationship between QRS duration and severity of coronary artery disease (CAD) in acute anterior MI (AMI). Methods: A cross-sectional study was conducted at the Department of Cardiology, Sir Salimullah Medical College and Mitford Hospital, Dhaka, from November 2019 to October 2020. One hundred patients with first anterior MI, admitted within 12 hours of chest pain onset and treated with thrombolysis, were enrolled. Patients were stratified into two groups: QRS≤100 ms (normal) and QRS >100 ms (prolonged). CAD severity was assessed using Gensini score, with ≥36 indicating moderate-to-severe disease. Results: Patients with prolonged QRS duration were significantly more likely to have severe CAD, with an eightfold higher risk compared to those with normal QRS (95% CI: 3.2-19.3; p<0.001). Conclusions: Prolonged QRS duration on admission ECG is strongly associated with severe CAD in acute anterior MI, suggesting its value for early risk stratification.